Training on the Implementation of English Language Learning Based on the Pedagogical Grammar Approach at Institut Agama Islam Diniyyah Pekanbaru - Safriyani Novitri; Estika Satriani; Novia Nazirun (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the implementation of English language learning based on the pedagogical grammar approach at Institut Agama Islam Diniyyah Pekanbaru. The purpose of the study was to explore how this approach enhances students' understanding and application of English grammar in communication. The research aimed to identify effective strategies, challenges, and the overall impact of pedagogical grammar on language proficiency. A qualitative approach was employed, utilizing classroom observations, interviews with instructors, and student feedback to analyze the effectiveness of the pedagogical grammar framework. Lesson materials were designed to integrate grammatical concepts into communicative contexts, ensuring that students could apply rules in real-life language use. Data were collected from English language classes and analyzed to determine students' progress, engagement, and comprehension of grammatical structures. The findings indicate that incorporating pedagogical grammar significantly improved students’ grammatical accuracy and confidence in communication. The approach helped bridge the gap between theoretical knowledge and practical usage, fostering better retention and application of language rules. However, challenges such as limited instructional time and varying student proficiency levels were observed. Teachers reported that explicit grammar instruction, combined with contextualized practice, contributed to more effective learning outcomes. In conclusion, the study highlights the importance of pedagogical grammar in English language learning, demonstrating its effectiveness in improving students’ grasp of grammar for communication. It suggests that future training should focus on equipping educators with adaptable strategies to address diverse learning needs, ensuring a more comprehensive and student-centered approach to English instruction.